Melohemsines A-I, melodinus-type alkaloids from Melodinus hemsleyanus. Issue 95 (26th September 2016) - Zhang, Jian; Yun ding,; Huang, Xiao-Jun; Jiang, Ren-Wang; Wang, Ying; Sun, Ping-Hua; Fan, Run-Zhu; Zhang, Xiao-Qi; Ye, Wen-Cai
Abstract : Melohemsines A-I (1–9 ) were obtained from Melodinus hemsleyanus .1 is the first melodinus-type alkaloid possessing a 6/6/5/5/6/3 six ring skeleton system.2 and3 are the first natural melodinus-type alkaloids with a reduction of two carbon units at C-20. Abstract : Nine new melodinus-type alkaloids, melohemsines A-I (1–9 ), together with eight known ones were isolated from Melodinus hemselyanus . The structures of the new alkaloids, including their absolute configurations, were elucidated on the basis of comprehensive spectroscopic and electronic circular dichroism (ECD) analyses and X-ray diffraction. Compound1 is the first melodinus-type alkaloid with a 6/6/5/5/6/3 hexacyclic ring skeleton system. Compounds2–3 are the first natural melodinus-type alkaloids with a reduction in two carbon units at C-20.